Evaluation of the Implications of Big Data Analytics with Organizational Performance in Small and Medium Enterprises and Its Associated Role of Knowledge Management - Almrshed, Sattar Kadim Hachim; Al Shaalan, Abbas Abdulkhudhur Abdullah; Flayyih, Mustafa Razzaq (South Asian Journal of Social Sciences and Humanities, 2024)
Introduction: Big data are distinguished by their quantity, speed, variety, and reliability. Big  data presents opportunity for “small and medium-sized” businesses (SME), in addition to being  a reality for giant firms. The term "big data" denotes to the fact that numerous varieties of data  have become more easily accessible, and its consequences for various organizational types may  vary from one another. SME can benefit greatly from creating and utilizing big data. Aim and  objectives: The main purpose of the study is to assess the implications of “big data analytics” with organizational performance in small and medium enterprises and its associated role of  knowledge management. Methods: This study's main goal was to develop a big data KM model  for SME through an examination of several business situations. This study used the qualitative  analysis of data methodology. The study gathered examples of large data for SME, which it  then used to test a KM model. Data collection, coding, and analysis are the three main  components of qualitative data analysis. Results: Big data collection is a business endeavor for  SMEs. An SME needs to specify its big data plans and deal with all potential organizational  difficulties. Big data must be strategically used in a way that is consistent with the SME's  business strategy and embraces a long-term strategy for competitive sustainability. To tackle  the big data challenge, IT solutions are chosen based on the definition of data requirements.
Keywords: organizational performance; small enterprises; medium enterprises; knowledge management